European tobacco use : trends report 2019 (World Health Organization Regional Office for Europe, 2019)
Tobacco use represents an important public health issue worldwide, but particularly in the WHO European Region, where the highest levels of tobacco-use prevalence (over 29%) have been reported. Tobacco use causes a significant burden on health, imposes enormous economic costs to society, both directly from health-care needs and indirectly from loss of productivity, fire damage and environmental harm. This document, developed by the WHO Regional Office for Europe, provides the latest available data on the current situation and changes over time in tobacco-use monitoring, health impacts, prevalence of tobacco use, health systems’ response to the tobacco epidemic, and the role of human rights and health policy in increasing awareness of the circumstances and effects of tobacco use. It aims not only to give insights into trends of tobacco use and prospects for its future control, but also to be an advocacy tool to encourage dialogue among policy-makers, health professionals, tobacco users and other stakeholders.
Keywords: Smoking; užívání tabáku; Evropa; Tobacco Use; Smoke-Free Policy; Europe; Human Rights; Nicotiana; veřejné zdravotnictví; lidská práva; tabák; kouření; nekuřácká politika